WAYS TO RESTORE UKRAINE'S ENVIRONMENT IN THE POST-WAR PERIOD (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The environmental crisis in Ukraine caused by the war will have significant consequences for hundreds of years to come and will affect neighboring countries and the world at large. Obviously, it is impossible to return the environment to its pre-war state, but it is possible to activate all scientific potential and human resources to improve the situation and allow ecosystems to gradually rebalance. The purpose of the article is to identify the main directions for overcoming the environmental crisis in Ukraine in the post-war period. The article analyzes the environmental consequences of the war, presents research by Ukrainian and European scholars, and focuses on international cooperation in solving environmental problems. The main environmental challenges, including soil, water, and air pollution, destruction of forests, etc. are discussed. The publication outlines areas of environmental rehabilitation related to innovative technical activities, implementation of foreign experience, public initiative, and an expanded range of environmental education and awareness. Innovative approaches of Ukrainians to combat the environmental crisis related to water, soil and air purification are emphasized. The environmental problems in Ukraine during the war period and plans for environmental restoration in the postwar period are covered in the works of Ukrainian ecologists (T. Denysenko, O. Mudrak, O. Naidenova, S. Rudyshyn and others) and European ecologists (W. Filho, J. Eustachio, D. Pietrzyk-Reeves, J. Carbonell). The article provides a list of Ukrainian NGOs engaged in environmental protection activities and organizing various environmental public initiatives. Particular attention is paid to the results of a survey of the population of Vinnytsia, Lviv, and Khmelnytsky regions, which showed the readiness of the population to engage in environmental activities. The article focuses on raising the environmental awareness of citizens as a basis for sustainable development of the country. The article emphasizes the need for an integrated approach that combines public policy, research, civic initiatives and international cooperation to effectively restore Ukraine's environment in the postwar period.